Psychoacoustic and cognitive effects of brain oscillations during listening to Fatihah Chapter - Samhani, Ismail; Begum, Tahamina; Idris, Zamzuri; Juahir, Hafizan; Abdullah, Jafri Malin; Reza, Mohammed Faruque (Bangladesh Journal of Medical Science, 2019)
Abstract not available Bangladesh Journal of Medical Science Vol.18(3) 2019 p.665-667